The home independence program with non-health professionals as care managers: An evaluation - Lewin, Gill; Concanen, K.; Youens, David (Dove Medical Press Ltd., 2016)
The Home Independence Program (HIP), an Australian restorative home care/reablement service for older adults, has been shown to be effective in reducing functional dependency and increasing functional mobility, confidence in everyday activities, and quality of life. These gains were found to translate into a reduced need for ongoing care services and reduced health and aged care costs over time. Despite these positive outcomes, few Australian home care agencies have adopted the service model – a key reason being that few Australian providers employ health professionals, who act as care managers under the HIP service model. A call for proposals from Health Workforce Australia for projects to expand the scope of practice of health/aged care staff then provided the opportunity to develop, implement, and evaluate a service delivery model, in which nonprofessionals replaced the health professionals as Care Managers in the HIP service. Seventy older people who received the HIP Coordinator (HIPC) service participated in the outcomes evaluation. On a range of personal outcome measures, the group showed statistically significant improvement at 3 and 12 months compared to baseline. On each outcome, the improvement observed was larger than that observed in a previous trial in which the service was delivered by health professionals.However, differences in the timing of data collection between the two studies mean that a direct comparison cannot be made. Clients in both studies showed a similarly reduced need for ongoing home care services at both follow-up points. The outcomes achieved by HIPC, with non-health professionals as Care Managers, were positive and can be considered to compare favorably with the outcomes achieved in HIP when health professionals take the Care Manager role. These findings will be of interest to managers of home care services and to policy makers interested in reducing the long-term care needs of older community dwelling individuals.